A Regulatory Circuit Orchestrated by Novel-miR-3880 Modulates Mammary Gland Development - Zhang, Yue; Liu, Jidan; Li, Wenfei; Cao, Fangjun; Niu, Guanglin; Ji, Shengyue; Du, Xiaoyan; Cao, Binyun; An, Xiaopeng (Frontiers in Cell and Developmental Biology, 2020)
Milk casein and triglyceride content are important production traits in goats. Studies on mechanisms in milk casein secretion and mammary gland development is essential for milk goat breeding. miRNAs play an important role in goat lactation. While novel-miR-3880 is highly expressed at goat peak lactation stage, its molecular mechanism has not been studied. The purpose of the present study was to explore the relationship between novel-miR-3880 and lactation, as well as to construct a network among novel-miR-3880, ciRNA13761, and E74 like ETS transcription factor 2 (ELF2), thus further exploring their potential roles in milk components and mammary gland development. ELF2 was previously proven to be important in cell survival and proliferation, and 3′-UTR of ELF2 was predicted to have binding sites of novel-miR-3880. Our study found that the overexpression of novel-miR-3880 exerted anti-apoptotic and proliferative roles in GMEC, induced a boost in triglyceride synthesis, and caused a decrease in α s1-, α s2-, and β-casein, but an increase in κ-casein secretion. Furthermore, treatment in mice indicated that novel-miR-3880 could promote mammary gland development and extend the lactation period, while novel-miR-3880 expression was found to be suppressed by ciRNA13761 as a miRNA sponge. The present study explores a mechanism of triglyceride synthesis and casein secretion, and reveals a crosstalk between ciRNA13761/novel-miR-3880/ELF2 axis and PI3K/AKT/mTOR/S6K1 pathway, to gain a better understanding of lactation traits in dairy goats.